Human development and the economic growth in Malaysia / Mohd Adib Azhari Sazali - Sazali, Mohd Adib Azhari (2022)
The UNDP Human Development Index (HDI) is a composite measurement that uses results in life expectancy at birth, education, and per capita income as a reference for several elements of human development that are not directly connected to health and education (Fukuda-Parr 2003). The Human Development Index, a combination of measurements of life expectancy, education, and income is the most often used indicator of Africa's human development. Empowerment of this population may be achieved by efforts designed to improve core human abilities such as health, knowledge, and skills that can be used to improve investments in beneficial exercises, social, cultural, and political activities (Wilson, 1996).